2012
DOI: 10.1039/c2lc21085a
|View full text |Cite
|
Sign up to set email alerts
|

Label-free quantitation of peptide release from neurons in a microfluidic device with mass spectrometry imaging

Abstract: Microfluidic technology allows the manipulation of mass-limited samples and when used with cultured cells, enables control of the extracellular microenvironment, making it well suited for studying neurons and their response to environmental perturbations. While matrix-assisted laser desorption/ionization (MALDI) mass spectrometry (MS) provides for off-line coupling to microfluidic devices for characterizing small-volume extracellular releasates, performing quantitative studies with MALDI is challenging. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 52 publications
(89 reference statements)
1
66
0
Order By: Relevance
“…The Sweedler group demonstrated a method for quantitation of analyte concentration using MALDI to image adsorption of the analyte along a length of a PDMS microfluidic channel [66]. They demonstrated through simulations and experiments that the length of the channel containing analyte was linearly proportional to the concentration of analyte (Figure 22A).…”
Section: Microfluidics Coupled To Maldi-msmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sweedler group demonstrated a method for quantitation of analyte concentration using MALDI to image adsorption of the analyte along a length of a PDMS microfluidic channel [66]. They demonstrated through simulations and experiments that the length of the channel containing analyte was linearly proportional to the concentration of analyte (Figure 22A).…”
Section: Microfluidics Coupled To Maldi-msmentioning
confidence: 99%
“…(C) Calibration curve for relating the channel coverage length to the concentration of analyte. Adapted with permission from [66]. Copyright (2012) Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%
“…Quantitative analyses of released analytes can also be performed using a microfluidic platform hyphenated to MS. Zhong et al [102] developed a device for the quantification of peptides released from A. californica bag cell neurons. The device consisted of one serpentine channel treated with octadecyltrichlorosilane (OTS), used to collect the peptides at specific locations.…”
Section: Measuring Cellular Microenvironments Including Cellular mentioning
confidence: 99%
“…A number of lab-on-a-chip applications have focused efforts toward improving signaling molecule detection, including sample preparation on chip (Wei et al, 2010), surface modifications (Jo et al, 2007;Zhong et al, 2012), and on-chip detection (Dishinger et al, 2009). The Kennedy group (Dishinger et al, 2009) reported an automated approach that quantified insulin release from 15 single islet cells using an on-chip electrophoresis channel and an immune assay for detection.…”
Section: In Vitro Manipulation Of Neural Cells: Lab-on-chip Platformsmentioning
confidence: 99%
“…The Kennedy group (Dishinger et al, 2009) reported an automated approach that quantified insulin release from 15 single islet cells using an on-chip electrophoresis channel and an immune assay for detection. We reported a microfluidic system with C18 functionalized channels to capture and quantify neuropeptide release on-chip with MS detection (Zhong et al, 2012). Rather than quantifying the peptide level via MS peak height, the length of the channel producing appreciable peptide signal from adsorption was used as a measure of peptide amount in release.…”
Section: In Vitro Manipulation Of Neural Cells: Lab-on-chip Platformsmentioning
confidence: 99%